TWENTY YEARS OF ANALES DE PSICOLOGIA: A JOURNAL WITH ACADEMIC ROOTS (1984-2004) - Peñaranda Ortega, María; Quiñones Vidal, Elena; López García, Juan José (Anales de Psicología / Annals of Psychology, 2005)
This paper focuses on the publications of the journal Anales de Psicología, analysing the scientific growth in the field of psychology. The period of time studied covers the last 21 years evolution of the Journal, from 1984 to 2004, although we must realize that in 1988 this journal was not published, and for that reason we have just analysed 20 years. Regarding the bibliometric methodology, published researches have been analysed focusing on its number and average per year, authors per research, distribution of their productivity and collaboration links between them, disclosing the most relevant invisible schools. Moreover, it has been performed not only a detailed analysis of the institutions to which authors belong but also gender percentage between researchers who publish in Anales de Psicología.